Analisis Gangguan Fonologi Pelafalan /R/ Pada Gebian Dalam Podcast Kuy Entertainment: Kajian Psikolinguistik - Nurjanah, Siti; Camila, Ananda Cahya; Tisnasari, Sundawati (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to investigate the phonological problems associated with the pronunciation of the phoneme /r/ in Gebian's speech through the Kuy Entertainment podcast, using a qualitative descriptive approach in the field of psycholinguistics. Data were obtained from transcripts of Gebian's speech in podcast episodes which were analyzed through listening methods and note-taking. In this study, forms of disorders were found such as the omission and change of the phoneme /r/ into the phoneme /h/ and /l/. The results of the study revealed an inappropriate pronunciation pattern of the phoneme /r/ which occurred consistently in various speech contexts. This disorder indicates a possible relationship with psychological factors and suboptimal function of the speech organs. This study is expected to contribute to understanding language disorders in digital media and enrich psycholinguistic studies, especially in terms of pronunciation.